An easy gene assembling strategy for light-promoted transfection by combining host-guest interaction of cucurbit[7]uril and gold nanoparticles - Jianwei Du (Nature Portfolio, 2017)
Abstract Cucurbit[7]uril (CB[7]), a representative member of the host family cucurbit[n]uril, can host-guest interact with many guest molecules such as adamantane, viologen and naphthalene derivatives. This host-guest interaction provides an easy strategy in gene vector assembling. Furthermore, CB[7] can self-assemble on gold nanospheres (AuNSs). Herein, the combination of CB[7] and AuNSs provides both advantages of host-guest interaction and photo-thermal effect of AuNSs. In this study, polyethyleneimine (PEI) and polyethylene glycol (PEG) were separately interacted with CB[7] via host-guest interaction. Then by assembling on AuNSs, PEI and PEG were combined together to condense DNA into polyplexes as well as enhance circulation stability of the polyplexes. These gene vectors were found to have high cellular uptake efficiency and low cytotoxicity. Furthermore, the well distributed AuNSs in the polyplexes could transform light into heat under light exposure because of the photo-thermal effect. This was found to effectively promote the entry of gene into cytoplasm and highly enhanced gene transfection efficiency.